Grasps for handwriting: prevalence of different types among young adults - Sime, Mariana Midori; Magna, Luis Alberto; da Cruz, Daniel Marinho Cezar; Ferrigno, Iracema Serrat Vergotti (Revista de Terapia Ocupacional da Universidade de São Paulo, 2014)
For handwriting, mature grasps are considered the most effi cient and recommended by educators and therapists, as they demand less energy loss and less tension in the proximal region of the upper limb. Some people use other grasps patterns that are also functional, however it is unknown what problems that may arise from use of these grasps. Knowing the types of grasp in young adults can support researches that relates the grasp used during functional activities with its implications. This study, quantitative, descriptive, cross-sectional, population- based, identifi ed the types and prevalence of pencil grasps used by 806 adults university students, all right handed, of both genders, without functional impairment of the upper limbs. The handwriting activity was fi lmed, and the images were analyzed and identifi ed. The results revealed the most frequent pattern was the dynamic tripod grasp, followed by lateral tripod, both mature grasps. The transition grasps and variations was identifi ed in 34,86% of the sample. Future researches could include excessive use of body structures and injuries in the upper limb, helping to provide suitable guidelines for the prevention and rehabilitation treatments of injuries.